Childhood maltreatment and polygenic risk in bipolar disorders. (13th November 2019) - Aas, Monica; Bellivier, Frank; Bettella, Francesco; Henry, Chantal; Gard, Sebastien; Kahn, Jean‐Pierre; Lagerberg, Trine V.; Aminoff, Sofie R.; Melle, Ingrid; Leboyer, Marion; Jamain, Stéphane; Andreassen, Ole A.; et al.
Abstract: Background: Childhood maltreatment is a well‐known risk factor for developing a more severe and complex form of bipolar disorders (BD). However, knowledge is scarce about the interactions between childhood maltreatment and underlying genetic vulnerability on the clinical expression of BD. Method: We assigned a BD‐polygenic risk score (BD‐PRS), calculated from the Psychiatric Genomics Consortium, to each individual in a sample of 402 cases with BD. The lifetime clinical expression of BD was characterized using structured interviews and patients completed the Childhood Trauma Questionnaire (CTQ) to assess the severity of childhood maltreatment. Results: Cases who reported more severe childhood maltreatment had a lower BD‐PRS (rho = −0.12, P = .01), especially when considering emotional abuse (rho = −0.16, P = .001). An interaction between BD‐PRS and childhood maltreatment was observed for the risk of rapid cycling ( P = .01). No further interactions between BD‐PRS and childhood maltreatment were observed for other clinical characteristics (age at onset, suicide attempts, number of mood episodes, mixed features, substance use disorders and psychotic symptoms). Conclusion: Our study is the first to show that less genetic risk may be needed to develop a more unstable form of BD when exposed to childhood maltreatment. Our study supports childhood trauma as an independent risk factor for BD.